(untitled) (Journal of Social Sciences Review, 2023)
The current study sought to investigate and add critical consequences of work engagement to the literature on psychological capital in the healthcare sector of Pakistan. For better understanding of the mechanism, Positive Emotions (PE) is added as potential mediator between the relationship of psychological capital (PsyCap) and work engagement. Also, the moderating role of emotional intelligence is studied. A total of 370 registered nurses working in tertiary public and private hospitals of Lahore participated in the survey. Using convenience sampling technique, the data were collected through a standardized and structured questionnaire using cross-sectional time frame. Results revealed that PE partially mediated the relationship between PsyCap and work engagement. Moderation revealed a statistically significant moderation of EI between PsyCap and PE. Also, it was worth noting that mediating effect of positive emotions among psychological capital and work engagement was moderated by emotional intelligence at all three levels of moderation. Workplace interventions need to be developed and implemented to increase the psychological capital and work engagement of registered nurses. Findings from this research have implications for registered nurses and hospital management as well as the literature of positive psychology. The results underlined the vital role of sub dimensions of PsyCap, EI and PE in developing work engagement among registered nurses.